Equivalence partitioning and cognitive walkthrough testing on the training prama website - Siahaan, Ranty Deviana; Martua Panggabean, Risky Junior (Institute of Computer Science (IOCS), 2025)
The Prama Training Website, developed by PT. Triputra Karya Lestari, aims to support employee skill development. However, the platform is underutilized due to usability issues and non-functional features. To address these problems, a two-pronged evaluation approach was conducted: Functional Testing using the Equivalence Partitioning (EP) method, and Non-Functional Testing through Cognitive Walkthrough (CW). Testing was carried out in two iterative stages. In stage one, 127 issues were identified 31 from EP and 96 from CW, while stage two revealed 12 remaining issues. These findings informed the design of a high-fidelity prototype, which incorporated targeted improvements to interface functionality and usability. The development culminated in the implementation of a revised Front-End Final Prototype, providing a more intuitive and accessible user experience for employees